PENGARUH KEWAJARAN HARGA DAN CITRA PERUSAHAAN TERHADAP KEPUTUSAN PEMBELIAN ULANG PADA PENUMPANG MASKAPAI CITILINK INDONESIA - Fakhrudin, Arif (Jurnal Manajemen Bisnis, 2019)
This study aims to analyze the influence of price fairness, corporate image on the repurchase decision of the Citilink Indonesia. The samples used in this study is 55 samples with deploy the questionnaire to the user the Citilink Indonesia that meets the criteria. Analysis of data in this study uses the analysis multiple linier regression.The result inficated that all variabels is positif effect, and have a significant effect. Variabel price fairness have a significant partial effect on the repurchase decision, show by the value of tcount 3,016 is greater than ttable 2,005 and a significant value of 0,004 is smaller than 0,05 and on variabel corporate image have a significant partial effect on the repurchase decision, show by the value of tcount 4,094 is greater than ttable 2,005 and a significant value of 0,000 is smaller than 0,05. Variabel price fairness and variabel corporate image have a significant simultaneous effect on the repurchase decision. This is indicated by value of Fcount 15,741 is greater than Ftable 3,18 and a significant value of 0,000 is smaller than 0,05. The influence of price fairness, corporate image on the repurchase decision of the Citilink Indonesia is 37,7%. This is shown by the number R2 (R Square) is 0,377 or 37,7% , while the rest 62,3% influenced by other variables not examined.